Mental Health and Construction—Intervening to Prevent Collapse - Rosa M. Gonzalez-Guarda; Molly Hayes; Luke Smith (JAMA Health Forum, 2026)
This JAMA Forum discusses mental health and substance abuse problems among US construction workers and proposes a national strategy to ensure that evidence-based prevention, early identification, and treatment reach this population.